PD-L1 Expression in Urothelial Carcinoma With Predominant or Pure Variant Histology: Concordance Among 3 Commonly Used and Commercially Available Antibodies. (July 2019) - Reis, Henning; Serrette, Rene; Posada, Jennifer; Lu, Vincent; Chen, Ying-bei; Gopalan, Anuradha; Fine, Samson W.; Tickoo, Satish K.; Sirintrapun, Sahussapont J.; Iyer, Gopa; Funt, Samuel A.; Teo, Min Yuen; et al.
Abstract : The introduction of immune checkpoint blockade (ICB) therapy has transformed the management of advanced bladder cancer (BC). Despite its limitations, PD-L1 immunohistochemistry may serve as a predictive biomarker of anti-PD-L1/PD1 therapy. While urothelial carcinoma (UC) patients with predominant or pure variant histology (UCV) account for up to one-third of advanced cases, to date, most ICB BC studies have excluded patients with such histologies. To assess the potential utility of ICB in patients with UCV, we analyzed PD-L1 expression in UCV and compared 3 commonly used and commercially available PD-L1 antibodies. Full sections from 84 UCV cases were stained with clones SP263, 22C3, and SP142, all of which are considered predictive assays to identify UC patients who are more likely to respond to anti-PD-1/PD-L1 inhibitors durvalumab, pembrolizumab, and atezolizumab, respectively. Expression on tumor cells (TC) and tumor-infiltrating immune cells (IC) was assessed. Staining extent and characteristics were evaluated, and concordance among the 3 clones was determined at various cutoff points as used in previous studies in BC. We found that PD-L1 was expressed in a significant percentage of UCV cases at different cutoff points (cutoff 1% TC: 37% to 54%, cutoff 5% TC: 23% to 37%), with the highest expression in UC with squamous differentiation. These figures are equal to or higher than those for classic/pure UC (4% to 30%). The results suggest that patients with UCV may benefit from anti-PD-1/PD-L1 therapy and argue against the exclusion of UC with predominant or pure variant histology from clinical ICB studies. The highest expression in both TC and IC was observed with clone SP263, followed by 22C3 and SP142, and all clones showed strong agreement in a pairwise comparison, both in TC and IC ( R -values: 0.780 to 0.901), which indicates that all 3 clones are potentially useful in the evaluation of PD-L1 expression in UCV.